A tale of two coffees? Analysing interaction and futures market efficiency (2020)
Purpose: The purpose of this paper is to assess the informational efficiency of Arabica (other milds) and Robusta coffee futures markets in terms of predicting future coffee spot prices. Design/methodology/approach: Futures market efficiency is associated with the existence of a long-run equilibrium relationship between spot and future prices such that coffee futures prices are unbiased predictors of future spot prices. This study applies unit root testing to daily data for futures-spot price differentials. A range of maturities for futures contracts are considered, and the study also uses a recursive approach to consider time variation in futures market efficiency. Findings: The other milds and Robusta futures prices tend to be unbiased predictors for their own respective spot prices. The paper further finds that other milds and Robusta futures prices are unbiased predictors of the respective Robusta and other milds spot prices. Recursive estimation suggests that the futures market efficiency associated with these cross cases has increased, though with no clear link to the implementation of the 2007 International Coffee Agreement. Originality/value: The paper draws new insights into futures market efficiency by examining the two key types of coffee and analyses the potential interactions between them. Hitherto, no attention has been paid to futures contracts of the Robusta variety. The employment of unit root testing of spot futures coffee price differentials can be viewed as more stringent than an approach based on non-cointegration testing. © 2020, Emerald Publishing Limited.